2003
DOI: 10.1149/1.1579034
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Hectorite Clay as the Ionic Conductor in LiCoO[sub 2] Cathodes

Abstract: Cathodes based on LiCoO 2 that contain various lithium-conducting species ͑lithium hectorite, lithium Laponite, and lithiumexchanged Nafion͒ are studied in conjunction with lithium metal anodes and composite electrolytes based upon lithium hectorite clays as the charge carrier. Performance is compared to that of cells with a standard liquid electrolyte ͑i.e., LiPF 6 ϩ1:1 w/w ethylene carbonate:ethyl methyl carbonate͒. Effects on cathode capacity are examined for these variables: hot-press force used in constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…[1][2][3] Fortunately, for clays the intracrystalline reactivity allows for extensive variation of properties and functions post synthesis. [4][5][6][7] For instance the ionic conductivity may be optimized for battery applications, 8 the mechanical properties of clay platelets may be tuned by controlled exfoliation, 9 or aspect ratios may be maximized via osmotic swelling. 10 Exfoliation into thinner tactoids or delamination into singular 2 : 1-lamellae represents an anisotropic top-down process (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Fortunately, for clays the intracrystalline reactivity allows for extensive variation of properties and functions post synthesis. [4][5][6][7] For instance the ionic conductivity may be optimized for battery applications, 8 the mechanical properties of clay platelets may be tuned by controlled exfoliation, 9 or aspect ratios may be maximized via osmotic swelling. 10 Exfoliation into thinner tactoids or delamination into singular 2 : 1-lamellae represents an anisotropic top-down process (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike in cells with intercalation cathodes, where Li + inserts and remains a cation and the charge compensation occurs on the transition metal and oxygen, 16,17 in cells with gold cathodes Li + is reduced to neutral metallic Li 0 , which alloys with the gold. The authors speculate that the polarization found in the intercalation cathodes ͑in this study and in the examples cited from the literature [2][3][4] ͒ is the result of coulombic attraction between the Li + attempting to intercalate and the bound anion in the electrolyte, which is free to approach the positively charged cathode thanks to the segmental mobility of the polymer backbone. The attractive electrostatic force between the bound anion and the Li + attempting to intercalate would thus represent an additional activation barrier to the ingress of lithium at the electrode/ electrolyte interface and would manifest itself in the form of polarization, i.e., an activation overpotential.…”
Section: Resultsmentioning
confidence: 74%
“…Recently, Riley et al presented a detailed study of the cycling behavior of a composite single-ion conducting electrolyte comprising 0.5 M Li hectorite in propylene carbonate ϳ0.48 g Li hectorite/g PC in batteries fitted with lithium anodes and composite LiCoO 2 cathodes. 4 They concluded that in these clay-based cells the values of the bulk electrolyte resistance as well as of the cathode charge-transfer resistance, cathode electronic/ionic resistance, and electrolyte/cathode surface-layer resistance were considerably higher than those for standard cells containing 1 M LiPF 6 in 1:1 w/w ethylene carbonate-:ethyl methyl carbonate. Clearly, even though the specific chemistries of the single-ion conducting electrolytes in these three studies varied considerably, in all cases when cells fitted with intercalation cathodes were cycled, an unanticipated increase in polarization was observed.…”
mentioning
confidence: 96%
“…Cation exchange strategies allow one to effectively replace the Na ions in hectorite by Li ions; also larger inorganic or organic molecules (pillars) can be introduced, resulting in porous so-called pillared clays . Exemplarily, the Khan group successfully used hectorite-based materials as passive and active filler materials to prepare nanocomposite polymer-based (gel) electrolytes as well as to develop composite LiCoO 2 -based cathode materials. Here, our hypothesis is that the interlayer gap in such host structures, particularly that of hectorite, offers indeed fast diffusion pathways for small charge carriers such as Li + and Na + ions.…”
Section: Introductionmentioning
confidence: 99%